Commercial Vegetable Fertilization Principles - G.J. Hochmuth; E.A. Hanlon (EDIS, 2016)
Farmers must carefully plan their fertilization programs, including conducting soil tests before planting. Investing in soil testing and adhering to BMPs can lead to substantial long-term benefits. This publication addresses vegetable fertilization in Florida, offering principles and methods for effective fertilization programs applicable to various crops. This document was first published in June 1996.